Expanded circulating peripheral helper T cells in primary biliary cholangitis: Tph cells in PBC. (March 2021) - Yong, Liu; Chunyan, Wang; Yan, Yu; Wanyu, Li; Huifan, Ji; Pingwei, Zhao; Yanfang, Jiang
Highlights: The frequencies of circulating TPH cells, ICOS + TPH cells, and CD28 + TPH cells were higher in PBC patients. Higher levels of ICOS + TPH and CD28 + TPH cell in cirrhotic patients than in noncirrhotic patients. TPH cell activation status is associated with the severity of PBC. Abstract: Background: Peripheral helper T (TPH) cells, a recently defined subset of Th cells, promote B cell differentiation and antibody production in inflamed tissues. This study investigated whether circulating TPH cells are associated with primary biliary cholangitis (PBC), a typical organ-specific autoimmune disease. Methods: Twenty PBC patients and 20 age- and sex-matched healthy controls (HCs) were recruited. The circulating TPH cell subsets were analyzed by flow cytometry, and the associations of TPH cells with disease activity and plasma cells were determined. Functional analysis was performed using a TPH and B cell coculture experiment. Results: The frequencies of circulating TPH cells, ICOS + TPH cells, and CD28 + TPH cells were increased in patients with PBC. Furthermore, the ICOS + TPH cell level was higher in PBC patients with or without cirrhosis than in HCs, and the level decreased after treatment. Moreover, ICOS + TPH cell levels correlated positively with specific clinical parameters (including anti-mitochondrial antibodies against M2 antigen (AMA-M2), IgM) and plasma cell levels, suggesting that the TPH cell activation status is associated with the severity of PBC. Coculture results revealed an enhanced ability of TPH cells from PBC patients to induce B cell differentiation. Conclusions: Elevated numbers of TPH cells may be involved in the pathogenesis of PBC, and the activation status of TPH cells is related to the severity of PBC. Additionally, TPH cells can be used as a useful biomarker for evaluating the progression of PBC and may serve as a therapeutic target for PBC patients in the future.